A FOOD LOSS BEHAVIOR MODEL FOR MICRO, SMALL AND MEDIUM ENTERPRISES IN AN AGRICULTURAL SUPPLY CHAIN - Noor, Vicky Rizky; Octavia, Johanna Renny; Sitompul, Carles (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
The study about supply chain is always interesting especially in the Micro, Small, and Medium Enterprises (MSMEs). This study is based on the phenomenon that MSME, especially from the production, post- harvest, and packaging section, is contributing the biggest food loss in a food supply chain in Indonesia. This paper tries to apply the extended theory of planned behavior as a framework to examine the behavior of MSME owners. The factors that are going to be examined are subjective norms, attitude towards behavior, perceived behavioral control, knowledge, spirituality, infrastructure, and price stability. The respondents of this study are the owners of MSME, especially the production, post-harvest, and packaging section of the food supply chain in West Java, Indonesia.